Lithium supplement and preparation method thereof, positive electrode sheet and secondary battery

The lithium supplement agent with a core composition of Li 5a+2b Fe a M b O 4a+2b addresses irreversible capacity loss in lithium-ion batteries by reducing gas production and residual alkali, enhancing the performance and stability of lithium-ion secondary batteries.

CN116505103BActive Publication Date: 2024-12-20SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310659133.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-20
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries suffer from irreversible capacity loss due to the formation of a solid electrolyte interface film (SEI film) during charging, leading to decreased coulombic efficiency, cycle life, and energy density, and current lithium replenishment materials have issues with low capacity, high residual alkalinity, and high gas production.

Method used

A lithium supplement agent with a core composition of Li 5a+2b Fe a M b O 4a+2b, where 0.5≤a<1, 0

Benefits of technology

The lithium supplement agent maintains high capacity, improves safety and electrochemical performance, and enhances the stability and processing performance of lithium-ion secondary batteries by minimizing gas production and residual alkali content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116505103B_ABST
    Figure CN116505103B_ABST
Patent Text Reader

Abstract

The present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate and a secondary battery. The lithium supplement agent includes a core, the core includes a first material phase, and the first material phase is Li 5a+2b Fe a M b O 4a+2b , wherein 0.5≤a<1, 0<b≤0.5, and a+b=1, and M is a reducing metal element. The lithium supplement provided in the present application can maintain a relatively high capacity level, and has a relatively low residual alkali value, and has a small amount of gas produced during charging, thereby improving the processing performance, safety performance and electrochemical performance of the lithium supplement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy technology, and in particular to a lithium supplement and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] During the first charge and discharge process of a battery such as a lithium-ion secondary battery, a large amount of solid electrolyte interface film (SEI film) will be produced on the surface of the negative electrode of the battery, which consumes the limited lithium ions and electrolyte in the battery, causing irreversible capacity loss, resulting in a decrease in the coulombic efficiency of the lithium-ion secondary battery, and directly affecting the cycle life and energy density of the lithium-ion secondary battery. At present, this part of the irreversible capacity loss can be eliminated by replenishing lithium at the positive electrode, thereby improving the battery energy density and other electrical properties. However, the existing lithium replenishment materials have the problems of low capacity or high residual alkalinity value and high gas production, which is not conducive to the promotion and application of lithium replenishment materials and limits the improvement of the performance of lithium-ion secondary batteries. Summary of the invention

[0003] The present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate and a secondary battery.

[0004] In a first aspect, the present application provides a lithium supplement agent, the lithium supplement agent comprising a core, the core comprising a first material phase, the first material phase being Li 5a+2b Fe a M b O 4a+2b , wherein 0.5≤a<1, 0<b≤0.5, and a+b=1, and M is a reducing metal element.

[0005] In the present application, the core of the lithium supplement comprises a chemical formula of Li 5a+2b Fe a M b O 4a+2b The first material phase has a low content of O and Li due to the addition of reducing metals. 5a+2b Fe a M b O 4a+2b The residual alkali value is low, and the gas production during charging is small, which improves the processing performance, safety performance and electrochemical performance of the lithium supplement. In the present application, controlling the Fe content to be greater than or equal to the M content can maintain a high capacity level of the lithium supplement, ensure the lithium supplement effect, and improve the stability of the lithium supplement.

[0006] In one embodiment, the reducing metal element includes at least one metal element selected from the group consisting of divalent nickel, divalent manganese, divalent iron, and divalent cobalt. Divalent nickel, divalent manganese, divalent iron, and divalent cobalt can reduce Li 5a+ 2b Fe a M bO 4a+2b The oxygen content makes the lithium supplement produce less gas during the charging process, thereby improving the safety and electrochemical performance of the lithium supplement.

[0007] In one embodiment, the core further includes a second material phase, and the second material phase is Li5FeO4. The second material phase can increase the capacity of the lithium supplement agent and achieve a better lithium supplement effect.

[0008] In one embodiment, the second material phase is doped with the first material phase. The second material phase and the first material phase are mixed to facilitate the preparation of the lithium supplement.

[0009] In one embodiment, the second material phase is filled in the gaps of the first material phase, thereby increasing the compaction density of the lithium supplement agent, which is beneficial to increasing the capacity of the lithium supplement agent and achieving a better lithium supplement effect.

[0010] In one embodiment, the first material is bonded to the outer surface of the second material phase. 5a+ 2b Fe a M b O 4a+2b The residual alkali value of the lithium supplement is lower than that of Li5FeO4. The first material phase is coated on the outer surface of the second material phase to reduce the overall residual alkali value of the lithium supplement, thereby improving the processing performance and safety performance of the lithium supplement.

[0011] In one embodiment, the core further includes a third material phase, the third material phase is Li2MO2, and the third material phase is bonded to the outer surface of the first material phase. The third material phase can reduce the gas production of the lithium supplement agent and improve the safety and electrochemical performance of the lithium supplement agent.

[0012] In one embodiment, the lithium supplement agent is further doped with a metal element, and the metal element includes at least one of aluminum, titanium, zirconium, vanadium, and manganese. Aluminum, titanium, zirconium, vanadium, manganese, cerium and other metal elements are doped in the lithium supplement agent to improve the structural stability of the lithium supplement agent or improve the conductivity of the material.

[0013] In one embodiment, the surface residual alkali value of the lithium supplement agent is 0%-1.5%.

[0014] In one embodiment, the particle size D50 of the lithium supplement agent is 0.5 μm-38 μm.

[0015] In one embodiment, the specific surface area of ​​the lithium supplement is 0.1 m 2 / g-20m 2 / g.

[0016] In one embodiment, the lithium supplement further includes a coating layer, which is located on the outer surface of the inner core and includes at least one of an isolation coating layer, an ion conductor coating layer, an electronic conductor coating layer, a single atom deposition layer, and an oxide nanofilm layer.

[0017] In one embodiment, the isolation coating layer includes at least one of a ceramic material, a high molecular polymer, and a carbon material.

[0018] In one embodiment, the electronic conductor coating layer comprises at least one of a carbon material, a conductive polymer, or a conductive oxide.

[0019] In one embodiment, the material of the ion conductor coating layer includes at least one of a perovskite-type, a NASICON-type, a garnet-type or a polymer-type solid electrolyte.

[0020] In one embodiment, the mass ratio of the core to the coating layer is 100:(0.01-15).

[0021] In one embodiment, the coating layer has a thickness of 1 nm to 400 nm.

[0022] In one embodiment, the water absorption rate of the lithium supplement agent is less than 20 ppm / s at 25° C. and 30%-35% relative humidity in air.

[0023] In one embodiment, the water absorption rate of the lithium supplement agent is less than 10 ppm / s at 25° C. and 30%-35% relative humidity in air.

[0024] In one embodiment, the water absorption rate of the lithium supplement agent is less than 10 ppm / s at 25° C. and 20%-25% relative humidity in air.

[0025] In one embodiment, the water absorption rate of the lithium supplement agent is less than 5 ppm / s at 25° C. and 20%-25% relative humidity in air.

[0026] In a second aspect, the present application provides a method for preparing a lithium supplement, the method for preparing the lithium supplement comprising:

[0027] Adding lithium source, iron source and M source into the complexing agent solution and stirring to obtain a gel;

[0028] The gel is sintered in a protective atmosphere to obtain the core of the lithium supplement agent.

[0029] Wherein, the preparation method of the lithium supplement is used to prepare the lithium supplement as described above.

[0030] In one embodiment, the method for preparing the lithium supplement further comprises: mixing the core and the coating material, and sintering them under a protective atmosphere to obtain the lithium supplement.

[0031] In a third aspect, the present application provides a method for preparing a lithium supplement, the method for preparing the lithium supplement comprising:

[0032] The solution of the iron source and the M source is mixed with the precipitant solution to precipitate and obtain a precursor;

[0033] After the lithium source and the precursor are mixed evenly, sintering is performed under a protective atmosphere to obtain the core of the lithium supplement agent;

[0034] Wherein, the preparation method of the lithium supplement is used to prepare the lithium supplement as described above.

[0035] In one embodiment, the method for preparing the lithium supplement further comprises: mixing the core and the coating material, and sintering them under a protective atmosphere to obtain the lithium supplement.

[0036] In a fourth aspect, the present application provides a positive electrode plate, wherein the positive electrode plate comprises the lithium supplement agent as described above, or comprises the lithium supplement agent prepared by the preparation method of the lithium supplement agent as described above.

[0037] In a fifth aspect, the present application provides a secondary battery, comprising a negative electrode plate, a separator, and the positive electrode plate as described above.

[0038] In one embodiment, the secondary battery is a lithium-ion battery, and in the lithium-ion battery, the first lithium desorption capacity of the lithium supplement agent is greater than or equal to 550 mAh / g.

[0039] In one embodiment, the ratio of the first-cycle gas production of the lithium supplement to the first-cycle gas production of the corresponding Li5FeO4 is less than or equal to 50%. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments of the present application will be described below.

[0041] Figure 1 is a schematic structural diagram of a lithium supplement provided by one embodiment of the present application;

[0042] Figure 2 This is an X-ray diffraction (XRD) diagram of a lithium supplement provided in one embodiment of the present application. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0044] In this document, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0045] In addition, in this article, directional terms such as "upper" and "lower" are defined relative to the orientation of the structure schematically placed in the drawings. It should be understood that these directional terms are relative concepts. They are used for relative description and clarification, and they can change accordingly according to the change of the orientation of the structure.

[0046] For ease of understanding, the English abbreviations and related technical terms involved in the embodiments of the present application are explained and described below.

[0047] Relative humidity: refers to the percentage of water vapor pressure in the air to the saturated water vapor pressure at the same temperature.

[0048] ppm: parts per million, which means one part per million. For gases, ppm refers to the molar fraction or volume fraction; for solutions, ppm refers to the mass concentration.

[0049] During the first charge and discharge process of a battery such as a lithium-ion secondary battery, a large amount of solid electrolyte interface film (SEI film) will be produced on the surface of the negative electrode of the battery, which consumes the limited lithium ions and electrolyte in the battery, greatly reducing the capacity of lithium ions and causing irreversible capacity loss. During the first discharge, the lithium ions extracted from the negative electrode are much smaller than the lithium ions extracted from the positive electrode during charging, resulting in a decrease in the coulombic efficiency of the lithium-ion secondary battery, which directly affects the cycle life and energy density of the lithium-ion secondary battery. To address this problem, the loss of this part of irreversible capacity can usually be eliminated by replenishing lithium at the positive electrode, thereby improving the battery energy density and other electrical properties. However, the existing lithium replenishment materials have the problems of low capacity, high residual alkalinity value and high gas production, which are not conducive to the promotion and application of lithium replenishment materials and limit the improvement of the performance of lithium-ion secondary batteries.

[0050] See also Figure 1 The present application provides a lithium supplement agent 1, the lithium supplement agent 1 includes a core 10, the core 10 includes a first material phase, the first material phase is Li 5a+2b Fe a M b O 4a+2b , wherein 0.5≤a<1, 0<b≤0.5, and a+b=1, and M is a reducing metal element.

[0051] Here, Li represents lithium, Fe represents iron, and O represents oxygen. The reducing metal is a metal with reducing properties, which is easy to combine with oxygen and can inhibit the generation of oxygen by the lithium supplement material.

[0052] The lithium supplement agent 1 is applied to the positive electrode of the battery to pre-lithiate the positive electrode, and lithium is added to the inside of the battery to supplement lithium ions before the battery is operated. In one embodiment, when the lithium supplement agent 1 is applied, the lithium supplement agent 1 can be applied to the outer surface of the positive electrode plate of the battery, or the lithium supplement agent 1 can be embedded in the outer surface of the positive electrode plate of the battery. In other embodiments, the lithium supplement agent 1 can also be added during the preparation process of the positive electrode plate of the battery, so that the lithium supplement agent 1 is dispersed on the outer surface and inside of the positive electrode plate of the battery.

[0053] The lithium supplement 1 includes a core 10 having a high lithium content. During the first charging process, the lithium (Li) in the core 10 can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, so as to improve the total capacity and energy density of the battery.

[0054] The lithium supplement agent 1 provided in the present application has a high lithium supplement capacity, produces less gas during charging, and has high safety performance.

[0055] In the prior art, lithium ferrite, lithium nickelate or lithium manganese oxide is usually used as the lithium supplement 1. When lithium ferrite (Li5FeO4) is used as the lithium supplement 1, the capacity of lithium ferrite is high, but the gas production of lithium ferrite is large during the charging process, which increases the battery impedance and reduces the battery safety and electrochemical performance. In addition, the residual alkali value of lithium ferrite is high, which easily causes gelation of the slurry during the slurry mixing process, and the slurry fluidity is poor, which seriously affects the processing performance of the lithium supplement 1. When lithium nickelate (such as Li2NiO2) or lithium manganese oxide (such as Li2MnO2) is used as the lithium supplement 1, although the gas production of lithium nickelate / lithium manganese oxide is small and the residual alkali value is low during the charging process, the capacity of lithium nickelate / lithium manganese oxide is low, and the lithium supplement effect is poor, which limits the improvement of battery performance.

[0056] In the present application, the chemical formula of the first material phase in the lithium supplement 1 is Li 5a+2b Fe a M b O 4a+2b , Li 5a+2b Fe a M b O 4a+2b It can maintain a high capacity level, and due to the addition of reducing metal elements, the activity of combining with water is reduced, Li 5a+ 2b Fe a M b O 4a+2bThe residual alkali value is low, and the gas production during charging is small, which improves the processing performance, safety performance and electrochemical performance of the lithium supplement agent 1. In the present application, the Fe content is controlled to be greater than or equal to the M content, which can ensure the lithium supplement effect of the lithium supplement agent 1 while improving the stability of the lithium supplement agent 1.

[0057] In one embodiment, the value range of a is 0.5≤a≤0.8. Within this range, the residual alkali value of the lithium supplement agent 1 is lower, the gas production is less, the lithium supplement agent 1 has better processing performance, safety performance and electrochemical performance, and the lithium supplement agent 1 not only has a good lithium supplement effect, but also has good stability.

[0058] In one embodiment, the reducing metal element includes at least one metal element selected from the group consisting of divalent nickel, divalent manganese, divalent iron, and divalent cobalt. 5a+2b Fe a Ni b O 4a+2b When M is selected from Mn, the chemical formula of the core 10 is Li 5a+2b Fe a Mn b O 4a+2b When M is selected from Ni and Mn, the chemical formula of the core 10 is Li 5a+ 2b Fe a Ni b1 Mn b2 O 4a+2b , where b1+b2=b.

[0059] Divalent nickel, divalent manganese, divalent iron, and divalent cobalt can reduce Li 5a+2b Fe a M b O 4a+2b The amount of gas produced during the charging process improves the safety and electrochemical performance of the lithium supplement 1.

[0060] In one embodiment, the core 10 further includes a second material phase, and the second material phase is Li5FeO4. The second material phase can increase the capacity of the lithium supplement agent 1 and achieve a better lithium supplement effect.

[0061] In one embodiment, the second material phase is doped with the first material phase. The second material phase and the first material phase are mixed to facilitate the preparation of the lithium supplement agent 1.

[0062] In one embodiment, the second material phase is filled in the gaps of the first material phase, thereby increasing the compaction density of the lithium supplement agent 1, which is beneficial to increasing the capacity of the lithium supplement agent 1 and achieving a better lithium supplement effect.

[0063] In one embodiment, the first material is bonded to the outer surface of the second material phase. 5a+2b Fe a M b O 4a+2b The residual alkali value of the lithium supplement 1 is lower than that of Li5FeO4, and the first material phase is coated on the outer surface of the second material phase to reduce the overall residual alkali value of the lithium supplement 1, thereby improving the processing performance and safety performance of the lithium supplement 1.

[0064] In one embodiment, the core 10 further includes a third material phase, which is Li2MO2, and the third material phase is bonded to the outer surface of the first material phase. The third material phase can reduce the gas production of the lithium supplement 1 and improve the safety and electrochemical performance of the lithium supplement 1.

[0065] In one embodiment, the lithium supplement 1 is further doped with a metal element, and the metal element includes at least one of aluminum, titanium, zirconium, vanadium, manganese, and cerium. The metal elements such as aluminum, titanium, zirconium, vanadium, manganese, and cerium are doped in the lithium supplement 1 to improve the structural stability of the lithium supplement 1.

[0066] In one embodiment, the residual alkali value on the surface of the lithium supplement 1 is 0%-1.5%. The residual alkali value on the surface of the lithium supplement 1 affects its processing performance and stability. It is understandable that the higher the residual alkali value on the surface of the lithium supplement 1, the stronger the alkalinity of the lithium supplement 1, the poorer the stability of the lithium supplement 1, and the lithium supplement 1 is easy to react with air and electrolyte, which directly affects the electrochemical properties of the lithium supplement 1 and reduces the safety performance of the battery. In addition, the high residual alkali value on the surface of the lithium supplement 1 can easily cause gelation of the slurry during the slurry adjustment process, and the slurry fluidity is poor, which seriously affects the processing performance of the lithium supplement 1.

[0067] The surface residual alkali value of the lithium supplement agent 1 provided in the present application is in the range of 0%-1.5%. The surface residual alkali value of the lithium supplement agent 1 is low, which improves the stability and processing performance of the lithium supplement agent 1, so that the lithium supplement agent 1 can achieve the function of efficient lithium supplementation.

[0068] In one embodiment, the surface residual alkali value of the lithium supplement agent 1 is 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%.

[0069] In one embodiment, the residual alkali value on the surface of the lithium supplement agent 1 is 0%-1%. Within this range, the performance of the lithium supplement agent 1 is more excellent. More preferably, the residual alkali value on the surface of the lithium supplement agent 1 is 0%-0.5%.

[0070] In one embodiment, the particle size D50 of the lithium supplement 1 is 0.5 μm-38 μm. The particle size D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage in the lithium supplement 1 reaches 50%.

[0071] It is understandable that if the particle size of the lithium supplement agent 1 is too small, the lithium supplement agent 1 is easy to agglomerate, and the lithium inside the lithium supplement agent 1 is difficult to escape when the active lithium is supplemented to the negative electrode, thereby reducing the lithium supplement effect of the lithium supplement agent 1; and when the particle size of the lithium supplement agent 1 is too large, it is not conducive to the electronic conduction and ion conduction of the lithium supplement agent 1, and it is not conducive to the preparation of the slurry of the lithium supplement agent 1. When the lithium supplement agent 1 is coated on the positive electrode of the battery, the large particle size is easy to scratch the aluminum foil, which is not conducive to the preparation of the positive electrode sheet of the lithium supplement agent 1.

[0072] In this embodiment, the particle size D50 of the lithium supplement 1 is controlled between 0.5 microns and 38 microns, which can ensure the rapid release of lithium ions while improving the dispersibility of the lithium supplement 1, making it easier to use the lithium supplement 1 and protect the electrode.

[0073] In one embodiment, the particle size D50 of the lithium supplement 1 can be 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 29μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm or 38μm.

[0074] In one embodiment, the particle size D50 of the lithium supplement agent 1 is 3 μm-15 μm. Within this range, the performance of the lithium supplement agent 1 is more excellent.

[0075] In one embodiment, the specific surface area of ​​the lithium supplement 1 is 0.1 m 2 / g-20m 2 / g. In one embodiment, the specific surface area is measured by the BET (Brunauer-Emmett-Teller) specific surface area test method, and the specific surface area is the BET specific surface area. It is understandable that if the specific surface area of ​​the lithium supplement agent 1 is too small, it is not conducive to improving the conductivity and lithium ion extraction and insertion ability of the lithium supplement agent 1. If the specific surface area of ​​the lithium supplement agent 1 is too large, the density of the lithium supplement agent 1 is usually small and the volume energy density is low.

[0076] In this embodiment, the specific surface area of ​​the lithium supplement agent 1 is controlled to be 0.1 m 2 / g-20m 2 / g, not only the conductivity and lithium ion extraction and insertion ability of the lithium supplement agent 1 can be improved, but also the volume energy density of the lithium supplement agent 1 can be improved.

[0077] In one embodiment, the specific surface area of ​​the lithium supplement 1 can be 0.1 m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g or 20m 2 / g.

[0078] In one embodiment, the lithium supplement 1 further includes a coating layer 20, and the coating layer 20 is located on the outer surface of the core 10. The coating layer 20 can fully or partially cover the outer surface of the core 10. The coating layer 20 can protect the core 10. It is understandable that if the coating layer 20 is not coated and only the core 10 is used as the lithium supplement 1, on the one hand, the outer surface of the core 10 has residual alkali, which reduces the stability of the lithium supplement 1, and when the lithium supplement 1 is coated on the positive electrode of the battery for use, the lithium supplement 1 is more likely to cause gelation of the slurry during the slurry mixing process, and the slurry has poor fluidity, which affects the processing performance of the lithium supplement 1. On the other hand, the surface of the lithium supplement 1 usually contains more free lithium, and a higher free lithium content will deteriorate the high-temperature storage performance of the battery, leading to problems such as flatulence and performance degradation during battery storage.

[0079] In the present application, on the one hand, the chemical formula of the core 10 is configured as Li 5a+2b Fe a M b O 4a+2b, while reducing the residual alkali value of the outer surface of the core 10, a coating layer 20 is provided on the outer surface of the core 10 to further reduce the residual alkali value of the lithium supplement 1, thereby improving the stability and processing performance of the lithium supplement 1. On the other hand, the coating layer 20 reduces the free lithium content on the outer surface of the lithium supplement 1, thereby facilitating the storage of the lithium supplement 1.

[0080] In one embodiment, the coating layer 20 includes at least one of an isolation coating layer 21, an ion conductor coating layer 22, an electronic conductor coating layer 23, a single atom deposition layer, and an oxide nanofilm layer.

[0081] In one embodiment, the coating layer 20 is an isolation coating layer 21. The isolation coating layer 21 can isolate the core 10 from moisture and carbon dioxide. The isolation coating layer 21 can protect the core 10 and improve the stability of the core 10 to ensure the lithium supplementation effect of the core 10. At the same time, it ensures the stability and uniformity of the lithium supplementation of the lithium supplement agent 1 in the electrode active slurry and active layer, as well as good processing performance. The isolation coating layer 21 can be located on the outer surface of part of the core 10, or it can cover the entire outer surface of the core 10, and the present application does not limit this.

[0082] In one embodiment, the isolation coating layer 21 includes at least one of a ceramic material, a polymer, and a carbon material. Among them, the ceramic includes at least one of alumina, silicon dioxide, boehmite, silicon nitride, silicon carbide, and boron nitride. The polymer includes one or more of polyvinylidene fluoride, sodium alginate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid salt, polyacrylonitrile, polyamide, polyimide, polyvinyl pyrrolidone, polyethylene oxide (PEO), polypyrrole (PPy), polytetrafluoroethylene (PTFE), and polyurethane (PU). The carbon material includes at least one of graphene, carbon nanotubes, carbon nanospheres, carbon nanofibers, graphite, and carbon black.

[0083] In one embodiment, the coating layer 20 is an ion conductor coating layer 22. The ion conductor coating layer 22 can enhance the ion conductivity of the lithium supplement 1. The ion conductor coating layer 22 is conducive to the outward transport of lithium ions in the lithium supplement 1; at the same time, the ion conductor coating layer 22 can also play an auxiliary role in enhancing ion transport inside the electrode. The ion conductor coating layer 22 can be a dense structure or a loose structure, and can be fully coated on the outer surface of the core 10 or partially coated on the outer surface of the core 10.

[0084] In one embodiment, the material of the ion conductor coating layer 22 includes at least one of a perovskite type, a NASICON type, a garnet type or a polymer type solid electrolyte. 3x La 2 / 3-x TiO3(LLTO), specifically Li 0.5 La 0.5TiO3、Li 0.33 La 0.57 TiO3、Li 0.29 La 0.57 TiO3、Li 0.33 Ba 0.25 La 0.39 TiO3, (Li 0.33 La 0.56 ) 1.005 Ti 0.99 Al 0.01O3 , Li 0.5 La 0.5 Ti 0.95 Zr 0.05 O3, etc. NASICON type such as but not only Li 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP). Garnet type includes Li7La3Zr2O 12 (LLZO), Li 6·4 Ln3Z 1·4 Ta 0·6 O 12 , Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 At least one of the polymer solid electrolytes includes at least one of PEO / PPO / PVDF etc. which dissolves lithium salt.

[0085] In one embodiment, the coating layer 20 is an electronic conductor coating layer 23. The electronic conductor coating layer 23 can enhance the electronic conductivity of the lithium supplement 1. The electronic conductor coating layer 23 is conducive to reducing the impedance inside the electrode. At the same time, the electronic conductor coating layer 23 can also play an auxiliary role as a conductive agent inside the electrode. The electronic conductor coating layer 23 can be a dense structure or a loose structure, and can be fully coated on the outer surface of the core 10 or partially coated on the outer surface of the core 10.

[0086] In one embodiment, the electronic conductor coating layer 23 includes at least one of a carbon material, a conductive polymer, or a conductive oxide. The carbon material includes at least one of graphene, carbon nanotubes, carbon nanospheres, carbon nanofibers, graphite, and carbon black. The conductive polymer may be, but is not limited to, the conductive polymer contained in the isolation coating layer 21. The conductive oxide includes at least one of In2O3, ZnO, and SnO2.

[0087] In one embodiment, the coating layer 20 is a deposition layer, and the deposition layer includes a single atomic deposition layer and / or an oxide nanofilm layer obtained by atomic layer deposition technology. Specifically, the deposition layer can be a single atomic deposition layer obtained by atomic layer deposition technology, and the level can be a single atomic layer or nanolayer composed of atoms or molecules. Optionally, when the deposition layer is a single atomic deposition layer, different atomic deposition agents can be selected according to the different materials, including but not limited to one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tetrakis(diethylamino)titanium, triethylsilane, tetraethylsilane, and tetrakis(ethylmethylamino)zirconium.

[0088] Optionally, the deposited layer may also be an oxide nanofilm layer. For example, the oxide nanofilm layer may be a layer obtained by reacting the above-mentioned single atomic deposited layer with oxygen, and the specific material may be aluminum oxide, titanium dioxide, silicon dioxide, zirconium dioxide, etc. It may also be a nano-scale oxide layer directly formed on the outer layer of the inner core by vapor deposition technology. Of course, it may also be an oxide nanofilm layer obtained by other technologies.

[0089] In one embodiment, the coating layer 20 includes at least two of an isolation coating layer 21, an ion conductor coating layer 22, and an electron conductor coating layer 23. Exemplarily, in one embodiment, the coating layer 20 includes an isolation coating layer 21 and an ion conductor coating layer 22, and the ion conductor coating layer 22 is coated on the outer surface of the core 10, and the isolation coating layer 21 is coated on the outer surface of the ion conductor coating layer 22.

[0090] In one embodiment, the coating layer 20 includes an isolation coating layer 21 and an electronic conductor coating layer 23 , wherein the isolation coating layer 21 is coated on the outer surface of the core 10 , and the electronic conductor coating layer 23 is coated on the outer surface of the isolation coating layer 21 .

[0091] In one embodiment, the coating layer 20 includes an isolation coating layer 21, an ion conductor coating layer 22, and an electronic conductor coating layer 23 (such as Figure 1 As shown), the ion conductor coating layer 22 is coated on the outer surface of the core 10, the isolation coating layer 21 is coated on the outer surface of the ion conductor coating layer 22, and the electronic conductor coating layer 23 is coated on the outer surface of the isolation coating layer 21.

[0092] In one embodiment, when the coating layer 20 includes two or more coating layers 20, the coating sequence between the coating layers 20 can be set as needed and is not limited to the types listed above.

[0093] In one embodiment, the mass ratio of the core 10 to the coating 20 is 100:(0.01-15). The mass ratio of the core 10 to the coating 20 affects the performance of the lithium supplement 1. If the coating 20 content is too low, the coating 20 has a weak force, and it is difficult for the coating 20 to isolate the core 10 from the external environment, and it cannot play a good role in protecting the core 10 and improving the electronic conductivity or ion conductivity of the lithium supplement 1. If the coating 20 content is too high, it will reduce the proportion of the lithium supplement 1 in the positive electrode material, thereby reducing the amount of lithium supplement, and also increase the processing difficulty of the lithium supplement 1.

[0094] In this embodiment, the mass ratio of the core 10 to the coating layer 20 is controlled within the range of 100:(0.01-15). The appropriate mass ratio of the coating layer 20 can, on the one hand, make the lithium supplement 1 have better processing performance and improve the bonding force between the coating layer 20 and the core 10; on the other hand, the coating layer 20 will not increase the mass of the lithium supplement 1 too much, avoiding the coating layer 20 being too large and affecting the energy density of the lithium supplement 1 and reducing the capacity. On the other hand, the coating layer 20 can better isolate the core 10 from the external environment to protect the core 10 and improve the electronic conductivity or ionic conductivity of the lithium supplement 1.

[0095] In one embodiment, the mass ratio of the core 10 to the coating layer 20 is 100:0.01, 100:0.05, 100:0.1, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14 or 100:15.

[0096] In one embodiment, the mass ratio of the core 10 to the coating layer 20 is 100:(0.01-10). Within this range, the new energy of the lithium supplement 1 is more excellent. More preferably, the mass ratio of the core 10 to the coating layer 20 is 100:(0.01-5).

[0097] In one embodiment, the thickness of the coating layer 20 is 1nm-400nm. The thickness of the coating layer 20 affects the performance of the lithium supplement 1. If the thickness of the coating layer 20 is small, it is difficult for the coating layer 20 to isolate the core 10 from the external environment, and it cannot play a good role in protecting the core 10 and improving the electronic conductivity or ionic conductivity of the lithium supplement 1. If the thickness of the coating layer 20 is too large, it will reduce the proportion of the lithium supplement 1 in the positive electrode material, thereby reducing the amount of lithium supplementation, and also increase the interface resistance of the core 10 and increase the processing difficulty of the lithium supplement 1.

[0098] In this embodiment, the thickness of the coating layer 20 is controlled within the range of 1nm-400nm. The appropriate thickness of the coating layer 20 can, on the one hand, make the lithium supplement agent 1 have better processing performance and improve the bonding force between the coating layer 20 and the core 10; on the other hand, the coating layer 20 will not increase the mass of the lithium supplement agent 1 too much, avoiding the coating layer 20 being too heavy and affecting the energy density of the lithium supplement agent 1 and reducing the capacity. On the other hand, the coating layer 20 can better isolate the core 10 from the external environment, so as to protect the core 10 and improve the electronic conductivity or ionic conductivity of the lithium supplement agent 1.

[0099] In one embodiment, the coating layer 20 has a thickness of 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, or 400 nm.

[0100] In one embodiment, the water absorption rate of the lithium supplement 1 in air at 25°C and 30%-35% relative humidity is less than 20ppm / s. The water absorption rate of the lithium supplement 1 affects the processing performance and stability of the lithium supplement 1. Generally, the greater the water absorption rate of the lithium supplement 1, the faster the lithium supplement 1 absorbs water vapor in the air, and the lithium supplement 1 is very easy to react with environmental moisture and form a large amount of residual alkali on the surface, making the lithium supplement 1 alkaline. When the amount of residual alkali is too high, the stability of the lithium supplement 1 is poor, and it is easy to react with air and electrolyte, which directly affects the electrochemical performance of the lithium supplement 1 and reduces the safety performance of the battery.

[0101] In the present embodiment, the water absorption rate of the lithium supplement 1 is less than 20ppm / s in the air at 25°C and 30%-35% relative humidity. The water absorption rate of the lithium supplement 1 is controlled to be low, ensuring that the lithium supplement 1 does not quickly absorb moisture in the air, which is beneficial to ensure that the lithium supplement 1 is effectively isolated from water vapor, protect the stability of the core 10, and ensure the gram capacity of the lithium supplement 1, so as to achieve efficient lithium supplementation.

[0102] In one embodiment, the water absorption rate of the lithium supplement agent 1 in air at 25°C and 30%-35% relative humidity is 20ppm / s, 19ppm / s, 18ppm / s, 17ppm / s, 16ppm / s, 15ppm / s, 14ppm / s, 13ppm / s, 12ppm / s, 11ppm / s, 10ppm / s, 9ppm / s, 8ppm / s, 7ppm / s, 6ppm / s, 5ppm / s, 4ppm / s, 3ppm / s, 2ppm / s or 1ppm / s, which may easily cause gelation of the slurry during the slurry preparation process, resulting in poor slurry fluidity and seriously affecting the processing performance of the lithium supplement agent 1.

[0103] In one embodiment, the water absorption rate of the lithium supplement agent 1 in air at 25° C. and 30%-35% relative humidity is less than 10 ppm / s. Under this condition, the performance of the lithium supplement agent 1 is more excellent.

[0104] In one embodiment, the water absorption rate of the lithium supplement agent in air at 25°C and 20%-25% relative humidity is less than 10ppm / s. The water absorption rate of the lithium supplement agent 1 affects the processing performance and stability of the lithium supplement agent 1. In this embodiment, the water absorption rate of the lithium supplement agent 1 is controlled to be low to ensure that the lithium supplement agent 1 does not quickly absorb moisture in the air, which is conducive to ensuring that the lithium supplement agent 1 is effectively isolated from water vapor, protecting the stability of the core 10, and ensuring that the gram capacity of the lithium supplement agent 1 is exerted to achieve efficient lithium supplementation.

[0105] In one embodiment, the water absorption rate of the lithium supplement agent 1 in air at 25° C. and 20%-25% relative humidity is 10 ppm / s, 9 ppm / s, 8 ppm / s, 7 ppm / s, 6 ppm / s, 5 ppm / s, 4 ppm / s, 3 ppm / s, 2 ppm / s or 1 ppm / s.

[0106] In one embodiment, the water absorption rate of the lithium supplement agent in air at 25° C. and 20%-25% relative humidity is less than 5 ppm / s. Under this condition, the performance of the lithium supplement agent 1 is more excellent.

[0107] In one embodiment, the water absorption test method is as follows:

[0108] First, control the room humidity at 25°C, 20-25% or 30-35% relative humidity.

[0109] Second, take out 0.3-0.5g of sample from the glove box, one sample at a time, and take out another sample from the glove box after the test.

[0110] Third, place the weighing bottle in an analytical balance with a precision of 1 part per 100,000, close the door, and reset to zero.

[0111] Fourth, weigh 0.17-0.19 grams of the sample to be tested into the container, spread the material with a spoon, close the door, stabilize for 3-5 seconds, turn on the timer, and record the mass of the analytical balance as the value of 0min. Then record the values ​​of 5, 10, 15, and 20min respectively, and calculate the average absorption data for 10-20 minutes.

[0112] Calculation formula:

[0113] Unit: ppm / s.

[0114] The present application provides a method for preparing a lithium supplement 1. The method for preparing a lithium supplement 1 is used to prepare the lithium supplement 1 as described above. The method for preparing a lithium supplement 1 comprises steps S1-1 and S2-1. The specific steps are as follows:

[0115] Step S1-1, adding a lithium source, an iron source and an M source into a complexing agent solution, and stirring to obtain a gel;

[0116] Step S2-1, sintering the gel in a protective atmosphere to obtain the core 10 of the lithium supplement agent 1.

[0117] In one embodiment, the method for preparing the lithium supplement agent 1 further includes step S3-1: mixing the core 10 and the coating material, and sintering them under a protective atmosphere to obtain the lithium supplement agent 1.

[0118] Wherein, the M source is a nickel source and / or a manganese source. In step S1-1, a lithium source, an iron source and an M source are added to a complexing agent solution to prepare a gel, in which the lithium source, the iron source and the M source are evenly mixed and have good dispersion, so as to form an ordered structure in subsequent sintering. In one embodiment, in step S1-1, a mixed solution of the lithium source, the iron source, the M source and the complexing agent can be stirred under low temperature heating conditions to facilitate the dissolution of the lithium source, the iron source and the M source, and at least part of the solution is evaporated to form a gel. Exemplarily, the heating temperature can be 60°C-90°C.

[0119] In step S2-1, the gel is sintered under a protective atmosphere to prevent the M source from being oxidized. In one embodiment, a protective gas is introduced in step S2-1 to control the oxygen content to be below 50 ppm. The lithium source, the iron source and the M source react at high temperature to generate a chemical formula of Li 5a+2b Fe a M b O 4a+2b of kernel 10.

[0120] In step S3-1, the coating material is a material that can form an isolation coating layer 21, an ion conductor coating layer 22, and an electronic conductor coating layer 23. Sintering the core 10 and the coating material under a protective atmosphere can prevent oxidation of the element M. In one embodiment, a protective gas is introduced in step S3-1 to control the oxygen content to be below 50 ppm.

[0121] In one embodiment, when the coating material is carbon, a carbon layer is formed on the outer surface of the core 10. The method of forming the carbon layer includes the following steps: dispersing the core 20 in a carbon source, and forming a carbon layer on the surface of the core 20 after carbonization.

[0122] It is worth noting that when the lithium supplement agent 1 does not require the coating layer 20, step S3-1 can be omitted.

[0123] In one embodiment, after obtaining the gel in step S1-1, the gel is dried. During the drying process, the iron compound is first precipitated to form a seed crystal, and then grows into a core. After drying to a certain extent, the iron and M compounds are precipitated together to form a coating layer. After drying, calcination is performed at 300-700°C to obtain a precursor, in which the first material in the precursor is combined with the outer surface of the second material phase. In one embodiment, the preparation method of the lithium supplement 1 also includes the step of doping with metal elements, as shown below: the obtained precursor is crushed, placed in anhydrous ethanol, and the surface doping element compound is added while stirring, and then dried while stirring. After drying, it is calcined at 800°C to obtain a material core with a surface coated with the doping element.

[0124] The lithium supplement agent 1 prepared in the present application contains a variety of heterogeneous elements, with high purity, low surface residual alkali value, high lithium supplement capacity, and the structure of the lithium supplement agent 1 is more stable, which can effectively reduce the release of oxygen species, thereby reducing the generation of gas. In addition, the coating layer contained on the surface of the lithium supplement agent 1 can effectively isolate moisture, oxygen, etc. from contacting the core 10, improve the structural stability of the lithium supplement agent 1, and achieve a stable lithium supplement effect. At the same time, it can also improve the electronic and ion conductivity of the lithium supplement agent 1, and increase the rate of lithium ion release during charging. The lithium supplement agent 1 provided in the present application has more excellent performance.

[0125] In one embodiment, the sintering temperature of the gel is 400° C.-1000° C., and the sintering time is 3 h-20 h.

[0126] In one embodiment, the sintering temperature of the core 10 and the coating material is 500° C.-800° C., and the sintering time is 1 h-10 h.

[0127] In one embodiment, the lithium source is one or more of lithium oxide, lithium hydroxide, lithium acetate, lithium carbonate, lithium fluoride, and lithium chloride.

[0128] In one embodiment, the iron source is one or more of ferric acetate, ferric nitrate, ferric sulfate, ferric hydroxide, ferric chloride, and ferric oxide.

[0129] In one embodiment, the manganese source is one or more of manganese acetate, manganese nitrate, manganese monoxide, manganese sulfate, manganese hydroxide, and manganese dichloride.

[0130] In one embodiment, the nickel source is one or more of nickel acetate, nickel nitrate, nickel oxide, nickel sulfate, nickel hydroxide, and nickel chloride.

[0131] In one embodiment, the complexing agent is at least one of citric acid, ammonium citrate, maleic acid, oxalic acid, ammonium oxalate, ascorbic acid, polyethylene glycol, polyvinyl pyrrolidone, glycerol, isopropanolamine, hydrogen peroxide, and the like.

[0132] In one embodiment, the complexing agent solution is a solution formed by dissolving the complexing agent in a solvent, wherein the solvent is one or more of methanol, glycerol, ethanol and water.

[0133] In one embodiment, the protective atmosphere is one or more of nitrogen, helium, argon, and neon.

[0134] The present application provides a method for preparing a lithium supplement 1. The method for preparing a lithium supplement 1 is used to prepare the lithium supplement 1 as described above. The method for preparing a lithium supplement 1 comprises steps S1-2 and S2-2. The specific steps are as follows:

[0135] Step S1-2, mixing the solution of the iron source and the M source with the precipitant solution, and precipitating to obtain a precursor;

[0136] Step S2-2, after the lithium source and the precursor are mixed, sintering is performed under a protective atmosphere to obtain the core 10 of the lithium supplement agent 1;

[0137] In one embodiment, the method for preparing the lithium supplement agent 1 further includes step S3-2: mixing the core 10 and the coating material, and sintering them under a protective atmosphere to obtain the lithium supplement agent 1.

[0138] Wherein, M source is nickel source and / or manganese source. The solution of iron source and M source refers to a solution containing both iron source and M source. In step S1-2, the solution of iron source and M source is mixed with precipitant solution, which means that the solution of iron source and M source is added to precipitant solution for precipitation reaction, or the precipitant solution is added to the solution of iron source and M source for precipitation reaction. After the precipitation reaction, filtering is performed to obtain a solid precursor in which the iron source and M source are uniformly mixed, and the precursor is an iron-based lithium supplement material precursor containing M.

[0139] In step S2-2, the lithium source and the precursor are mixed and sintered, and the lithium source reacts with iron and M to generate a chemical formula of Li 5a+ 2b Fe a M b O 4a+2b The core 10 is sintered in a protective atmosphere to prevent the M source from being oxidized. In one embodiment, a protective gas is introduced in step S2-2 to control the oxygen content to be below 50 ppm.

[0140] In step S3-2, the coating material is a material that can form an isolation coating layer 21, an ion conductor coating layer 22, and an electronic conductor coating layer 23. Sintering the core 10 and the coating material under a protective atmosphere can prevent oxidation of the M element. In one embodiment, a protective gas is introduced in step S3-2 to control the oxygen content to be below 50 ppm.

[0141] The lithium supplement agent 1 prepared in the present application contains a variety of heterogeneous elements, with high purity, low surface residual alkali value, high lithium supplement capacity, and the structure of the lithium supplement agent 1 is more stable, which can effectively reduce the release of oxygen species, thereby reducing the generation of gas. In addition, the coating layer contained on the surface of the lithium supplement agent 1 can effectively isolate moisture, oxygen, etc. from contacting the core 10, improve the structural stability of the lithium supplement agent 1, and achieve a stable lithium supplement effect. At the same time, it can also improve the electronic and ion conductivity of the lithium supplement agent 1, and increase the rate of lithium ion release during charging. The lithium supplement agent 1 provided in the present application has more excellent performance.

[0142] In one embodiment, the sintering temperature of the lithium source and the precursor is 600° C.-1000° C., and the sintering time is 1 h-24 h.

[0143] In one embodiment, the sintering temperature of the core 10 and the coating material is 500° C.-800° C., and the sintering time is 1 h-10 h.

[0144] In one embodiment, the lithium source is one or more of lithium oxide, lithium hydroxide, lithium acetate, lithium carbonate, lithium fluoride, and lithium chloride. The iron source is one or more of ferric acetate, ferric nitrate, ferric sulfate, ferric hydroxide, ferric chloride, and ferric oxide. The manganese source is one or more of manganese acetate, manganese nitrate, manganese monoxide, manganese sulfate, manganese hydroxide, and manganese dichloride. The nickel source is one or more of nickel acetate, nickel nitrate, nickel oxide, nickel sulfate, nickel hydroxide, and nickel chloride.

[0145] In one embodiment, the precipitant is at least one of aqueous ammonia, sodium hydroxide, potassium hydroxide, magnesium hydroxide, lithium hydroxide, and calcium hydroxide.

[0146] The present application provides a positive electrode plate, which includes the lithium supplement agent 1 as described above, or includes the lithium supplement agent 1 prepared by the preparation method of the lithium supplement agent 1 as described above.

[0147] The present application provides a secondary battery, which includes a negative electrode plate, a separator and the positive electrode plate as described above.

[0148] In one embodiment, the secondary battery is a lithium ion battery, in which the initial lithium desorption capacity of the lithium supplement agent 1 is greater than or equal to 550 mAh / g. The initial lithium desorption capacity of the lithium supplement agent 1 is relatively high, and a better lithium supplement effect can be achieved.

[0149] In one embodiment, the ratio of the first-cycle gas production of the corresponding Li5FeO4 is less than or equal to 50%. Compared with Li5FeO4, the first-cycle gas production of the lithium supplement 1 provided in the present application is lower, thereby improving the battery safety and electrochemical performance.

[0150] In order to illustrate the beneficial effects of the method of the present application, the present application also provides the following examples and comparative examples:

[0151] Example 1

[0152] Example 1 provides a lithium supplement agent, including a core and a coating layer, wherein the chemical formula of the core is Li 3.5 Fe 0.5 Ni 0.5 O3, the coating layer is carbon material, and the mass ratio of the core to the coating layer is 100:5.

[0153] The preparation method of the lithium supplement in Example 1 comprises the following steps:

[0154] Step 1, dissolving a citric acid complexing agent in an ethanol aqueous solution, and then dissolving lithium hydroxide: ferrous acetate: nickel acetate in a molar ratio of 7:1:1, and stirring the solution at 60-90° C. until a dry gel is formed.

[0155] Step 2, sintering the dry gel prepared in step 1 for 3-20 hours at 750° C. under a protective atmosphere with an oxygen content controlled below 50 ppm to prepare a core.

[0156] Step 3, uniformly mixing the core prepared in step 2 with the carbon source, and sintering at 300° C. under a protective atmosphere to obtain a lithium supplement material.

[0157] Example 2

[0158] Example 2 provides a lithium supplement agent, which is different from Example 1 in that the chemical formula of the core of the lithium supplement agent in Example 2 is Li 3.8 Fe 0.6 Mn 0.4 O 3.2 .

[0159] Example 3

[0160] Example 3 provides a lithium supplement agent, which is different from Example 1 in that the chemical formula of the core of the lithium supplement agent in Example 3 is Li 4.4 Fe 0.8 Ni 0.2 O 3.6 .

[0161] Example 4

[0162] Example 4 provides a lithium supplement agent, which is different from Example 1 in that the core of the lithium supplement agent in Example 4 contains Li 3.5 Fe 0.5 Ni 0.5 O3 phase and Li5FeO4 phase.

[0163] Example 5

[0164] Example 5 provides a lithium supplement agent, which is different from Example 1 in that the core of the lithium supplement agent in Example 5 contains Li 4.4 Fe 0.8 Ni 0.2 O 3.6 phase and Li2NiO2 phase.

[0165] Example 6

[0166] Example 6 provides a lithium supplement agent, which is different from Example 1 in that the core of the lithium supplement agent in Example 6 contains Li 4.4 Fe 0.8 Ni 0.2 O 3.6 phase and Li2MnO4 phase.

[0167] Example 7

[0168] Example 7 provides a lithium supplement, which is different from Example 1 in structure in that, in Example 7, the mass ratio of the core to the coating layer is 100:15.

[0169] Example 8

[0170] Example 8 provides a lithium supplement. The structure of the lithium supplement is different from that of Example 1 in that the lithium supplement is doped with the metal element cerium. In Example 8, the core is prepared by a coprecipitation method. The preparation method of the lithium supplement in Example 8 includes the following steps:

[0171] Step 1: drip ammonia water into a solution of ferric acetate, nickel acetate and cerium acetate, heat treat the mixed solution and perform a precipitation reaction to generate an iron-based lithium supplement material precursor containing Ni.

[0172] Step 2, mixing lithium hydroxide and the iron-based lithium supplement material precursor containing M in step 1 uniformly in a molar ratio, sintering the mixture at 600-1000° C. for 1-24 hours under a protective atmosphere, and then naturally cooling the mixture to obtain a core.

[0173] Step 3, mixing the core and the carbon source, sintering at 500-800° C. for 1-10 hours under a protective atmosphere to obtain a lithium supplement containing a coating layer structure.

[0174] Comparative Example 1

[0175] Comparative Example 1 provides a lithium supplement agent, which is different from Example 1 in structure in that, in Comparative Example 1, the core of the lithium supplement agent contains only the lithium-rich compound Li5FeO4.

[0176] Comparative Example 2

[0177] Comparative Example 2 provides a lithium supplement agent, which is different from the structure of Example 1 in that the core of the lithium supplement agent in Comparative Example 2 contains only the lithium-rich compound Li2.6 Fe 0.2 Ni 0.8 O 2.4 .

[0178] Comparative Example 3

[0179] Comparative Example 3 provides a lithium supplement agent, which is different from Example 1 in structure in that, in Comparative Example 3, the core of the lithium supplement agent contains only the lithium-rich compound Li2NiO2.

[0180] Comparative Example 4

[0181] No lithium supplement is added to the subsequent positive electrode plates.

[0182] The lithium supplement provided in the above examples and comparative examples are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:

[0183] Positive electrode sheet: a lithium supplement agent and lithium iron manganese phosphate are mixed in a mass ratio of 2:98 to obtain a mixture, the mixture is mixed with polyvinylidene fluoride and SP-Li in a mass ratio of 95:3:2 by ball milling to obtain a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, rolled, and vacuum dried at 110°C overnight to obtain a positive electrode sheet;

[0184] Negative electrode: graphite negative electrode;

[0185] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;

[0186] Diaphragm: Polypropylene microporous separator;

[0187] Lithium-ion battery assembly: preparation into battery soft pack.

[0188] Related performance tests

[0189] 1. Tests related to lithium supplements

[0190] The lithium supplement core materials in Examples 1 to 8 were subjected to X-ray diffraction (XRD) analysis, wherein the XRD pattern in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the core material of the lithium supplement contains the characteristic diffraction peaks of lithium ferrite Li5FeO4 and lithium nickelate Li2NiO2, and the observed diffraction peaks of Li5FeO4 and Li2NiO2 are strong and the intensities of the two are comparable, indicating that the core material of the lithium supplement contains lithium-rich compounds Li 3.5 Fe 0.5 Ni 0.5 O3.

[0191] The XRD patterns of other embodiments also have corresponding characteristic diffraction peaks.

[0192] The electrochemical performance of each lithium ion battery assembled in the above lithium ion battery embodiment was tested as shown in Table 1, and the test conditions were as follows:

[0193] Constant current and constant voltage charging, the first cycle charge and discharge voltage is 2.0-4.3V, the current is 0.1C, and the cut-off current is 0.01C.

[0194] The relevant performance test results are shown in Table 1 below:

[0195] Table 1 Performance test results

[0196]

[0197] It can be seen from Examples 1-8 and Comparative Example 1 that the addition of the lithium supplement can increase the initial charge capacity of the battery, which means that the lithium supplement provided in the present application can improve the battery performance.

[0198] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the core includes Li 5a+2b Fe a M b O 4a+2b , and meets 0.5≤a<1, 0<b≤0.5, and when a+b=1, the battery has a lower water absorption rate. And when the a value gradually increases, the battery's first charge gram capacity increases, the lithium replenishment gram capacity is greatly improved, the water absorption rate decreases, and the gas production only increases slightly. In addition, compared with Comparative Example 1, Examples 1-3 have lower gas production. Compared with Comparative Examples 2-3, Examples 1-3 have higher lithium replenishment gram capacity. In general, the Li 5a+2b Fe a M b O 4a+2b The core has better overall performance and a lower water absorption rate, which makes the battery have higher safety performance.

[0199] It can be seen from Example 1 and Example 4 that after adding Li5FeO4 phase to the core of the lithium supplement agent, the initial charge gram capacity of the battery increases, the lithium supplement gram capacity is greatly improved, the water absorption rate is lower, and the gas production does not change much. It can be seen that adding Li5FeO4 phase to the core of the lithium supplement agent is beneficial to improving the performance of the battery, especially increasing the lithium supplement gram capacity and reducing the water absorption rate.

[0200] From Examples 3 and 5-6, it can be seen that after adding Li2NiO2 phase or Li2MnO4 phase to the lithium supplement core, the gas production of the battery is greatly reduced, the first charge gram capacity and water absorption rate do not change much, but a certain amount of lithium supplement gram capacity is lost. And the Li2MnO4 phase can provide a lower water absorption rate and gas production. It can be seen that adding Li2NiO2 phase or Li2MnO4 phase to the lithium supplement core is beneficial to reducing the gas production of the battery.

[0201] It can be seen from Example 1 and Example 7 that, although increasing the coating thickness can reduce the water absorption rate and gas production of the battery to a certain extent, it reduces the lithium replenishment gram capacity and the initial charge gram capacity. It can be seen that the coating thickness can be appropriately controlled to reduce the water absorption rate and gas production while ensuring a high lithium replenishment gram capacity and initial charge gram capacity.

[0202] From Example 1 and Example 8, after cerium is doped into the lithium supplement, although the water absorption rate, lithium supplement gram capacity and first charge gram capacity of the battery do not change much, the lithium supplement after cerium doping has a lower gas production.

[0203] The lithium supplement agent and its preparation method, the positive electrode sheet and the secondary battery provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and embodiments of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technicians in this field, according to the idea of ​​the present application, there will be changes in the specific embodiments and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A lithium supplement, characterized in that: The lithium supplement includes a core, and the core includes a first material phase, and the first material phase is Li 5a+2b Fe a M b O 4a+2b , where 0.5 < a ≤ 0.8, 0.2 ≤ b < 0.5, and a + b = 1, M is a reducing metal element, and the reducing metal element includes at least one metal element of divalent nickel, divalent manganese, divalent iron, and divalent cobalt; The core further includes a second material phase, the second material phase is Li5FeO4, and the second material phase is doped in the first material phase; or The second material phase fills the gaps between the first material phases; or The first material is bonded to an outer surface of the second material phase.

2. The lithium supplement according to claim 1, characterized in that: The inner core further includes a third material phase, wherein the third material phase is Li2MO2, and the third material is bonded to the outer surface of the first material phase.

3. The lithium supplement according to claim 1, characterized in that: The lithium supplement is further doped with metal elements, and the metal elements include at least one of aluminum, titanium, zirconium, vanadium, manganese, and cerium.

4. The lithium supplement according to claim 1, characterized in that: The lithium supplement further includes a coating layer, which is located on the outer surface of the inner core, and includes at least one of an isolation coating layer, an ion conductor coating layer, and an electronic conductor coating layer.

5. The lithium supplement according to claim 4, characterized in that: The surface residual alkali value of the lithium supplement agent is 0%-1.5%; and / or The water absorption rate of the lithium supplement agent is less than 20 ppm / s in air at 25°C and 30%-35% relative humidity; and / or At 25° C. and 20%-25% relative humidity in air, the water absorption rate of the lithium supplement agent is less than 10 ppm / s.

6. A method for preparing a lithium supplement, characterized in that: The preparation method of the lithium supplement agent is used to prepare the lithium supplement agent according to any one of claims 1 to 5, and the preparation method of the lithium supplement agent comprises: adding a lithium source, an iron source and an M source to a complexing agent solution, stirring to obtain a gel; sintering the gel in a protective atmosphere to obtain a core of the lithium supplement agent; or The preparation method of the lithium supplement agent comprises: mixing solutions of an iron source and an M source with a precipitant solution to obtain a precursor by precipitation; and mixing the lithium source and the precursor uniformly, and sintering them under a protective atmosphere to obtain the core of the lithium supplement agent.

7. A positive electrode sheet, characterized in that: The positive electrode plate includes the lithium supplement agent according to any one of claims 1 to 5, or includes the lithium supplement agent prepared by the preparation method of the lithium supplement agent according to claim 6.

8. A secondary battery, characterized in that: The secondary battery comprises a negative electrode sheet, a separator and the positive electrode sheet as claimed in claim 7.

9. The secondary battery according to claim 8, wherein the secondary battery is a lithium-ion battery, wherein the lithium-supplementing gram capacity of the lithium-supplementing agent is greater than or equal to 550 mAh / g; and / or The ratio of the first-cycle gas production of the lithium supplement agent to the first-cycle gas production of the corresponding Li5FeO4 is less than or equal to 50%.